(untitled) (Academia Journal of Medicine, 2025)
Aim: This study aimed to evaluate and compare pain perception during the administration of local anesthetic solution using conventional syringes versus insulin syringes in pediatric patients aged 6-8 years. Materials and Methods: A total of 40 patients requiring maxillary local infiltration were recruited. Participants were randomly assigned to receive local anesthetic via either a conventional syringe or an insulin syringe. Pain perception was assessed using a Visual Analogue Scale (VAS), where 0 represented no pain and 10 represented the worst pain imaginable. Measurements were taken immediately following the administration of the anesthetic. Results: The analysis of the VAS scores demonstrated that patients who received the anesthetic via insulin syringes reported significantly lower pain levels compared to those who received it via conventional syringes (p < 0.05). The results indicate a clear preference for the insulin syringe method, suggesting reduced pain perception. Conclusion: The study concluded that the use of insulin syringes for local anesthetic administration in pediatric dental procedures may lead to a significantly lower pain experience compared to conventional syringes.